ANDROID-BASED INTERACTIVE SCIENCE LEARNING (GeNda MaHiLingTar): AN APPLICATION DEVELOPMENT - Ririn Isna Magfiroh; Adinda Ayu Kisdiyanti; Achmad Ali Fikri (Universitas Pakuan, 2020)
Along with the development technology , teachers should make interesting and interactive science teaching materials for increase interest study students . There are many media that can be used for support learning IPA.iSpring is a device soft supporters who can help the teacher in resolve problem that . because _ that , research this aim for develop application interactive science learning for increase interest and understanding learn science at MTs Nurul Burhan Blingoh Donorojo on the subject of Motion of Objects and Living Things in the Environment Approx . With method RnD 3D model research has conducted from September to December 2021. Results of study this is said to be valid because results validation and eligibility above 80%, based on criteria feasibility of learning media and results from percentage Validation media expert and expert Theory of 86.17% and the percentage of the feasibility test product 80.27%.